Noise Enhanced Imaging of Weak Objects - Stephen Daedalus Separa; Giovanni Tapang; May Lim; Caesar Saloma (Science Diliman, 1999)
A method that allows the imaging of weak objects is demonstrated through the use of additive noise. Additive noise (characterized using a variance parameter a) is used to drive the intensity of the test object so that a threshold detector detects it. Performing the simulation with a sufficiently large number of trials decreases the optimum value of noise required for a good image quality.